Efek GCG Terhadap Manipulasi Profit Dengan Rasio Keuntungan Sebagai Intervening Pada Sektor Perbankan Yang Listed di BEI - Vishnu Pratama, Fajar; Gusmiarni, Gusmiarni; Hamilah, Hamilah (Rifa'Institute, 2022)
Profitability is one of the variables that is often studied in relation to profit manipulation. If the company has sufficient profitability, the company has the opportunity to maintain its business continuity. It is stated that potential investors will carefully analyze the smooth running of a company and its ability to earn profitability gains, because they expect dividends and market prices from their shares. Profit manipulation carried out by the management can be minimized by implementing GCG. For this reason, management is given some power to make the best decisions for shareholders. The purpose of this study is to analyze the effect of GCG on profit manipulation and the profit ratio as an intervening variable. The population in this study consisted of 10 (ten) bank sectors listed on the IDX. The data processing method uses Eviews10, data processing techniques with statistics, then classical assumptions, after that panel data and path regression. The results of this study indicate that institutional ownership has an effect on the profit ratio, while independent commissioners, audit committees, and independent commissioners have no effect on the profit ratio. directors, independent commissioners, audit committees, and institutional ownership together have an effect on the profit ratio. Directors, independent commissioners, audit committees, institutional ownership, and profit ratios have no effect on profit manipulation. The profit ratio is a mediator of the effects of the audit committee, institutional ownership on profit manipulation, while the profit ratio is not a mediator of the effects of independent commissioners and directors on profit manipulation